Pengembangan Materi Ajar Menulis Teks Eksposisi Berbasis Potensi Daerah Wajo di SMP - Ade Yustina; Ramly Ramly (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2021)
Research purpose to:(1) describe the form of teaching material to write exposition text based on the potential of Wajo area; and (2) testing the feasibility of teaching materials for writing exposition text based on the potential of the Wajo region. This type of research is research and development or Research and Development (R&D). The research design used is Recursive, Reflective Design, and Development Model (R2D2). The data in this study are qualitative and quantitative data from expert and practitioner assessments. Qualitative data sourced from comments, criticisms, and suggestions from expert and practitioner assessments of teaching material. Quantitative data sourced from expert and practitioner assessment scores on the components of teaching materials. The data analysis technique of this research is qualitative data analysis and quantitative data analysis. Qualitative data analysis is to group data and conclude data in the form of comments, criticisms, and suggestions from experts and practitioners for the improvement of teaching material. Quantitative data analysis is looking for the average of each indicator of expert and practitioner ratings for product viability. This research and development resulted in the teaching of Wajo Regional Potential Themed Text Exposition Texts for Class VIII Students of SMP / MTs that have been assessed by experts and practitioners. The results showed that the content eligibility component obtained an average of 0.93 (very feasible), a presentation component of 0.91 (very feasible), a linguistic component of 0.92 (very feasible), a graphic component of 0.94 (very feasible), and component implications for developing writing skills competence 0.94 (very feasible). The results of expert and practitioner assessments of teaching materials indicate that the assessment is in a very feasible category. Thus, teaching materials are recommended to be used as teaching materials in junior high schools.